Relationship between Muscle Function, Muscle Typology and Postural Performance According to Different Postural Conditions in Young and Older Adults - Paillard, Thierry (Frontiers in Physiology, 2017)
Although motor output of the postural function clearly influences postural performance in young and older subjects, no relationship has been formally established between them. However, the relationship between lower-extremity muscle strength/power and postural performance is often pointed out, especially in older subjects. In fact, the influence of motor output may vary according to the postural condition considered (e.g. static, dynamic, challenging, disturbing). In static postural condition, there may be a relationship between lower-extremity muscle strength and postural performance when the value of muscle strength is below a certain threshold in older subjects. Above this threshold of muscle strength, this relationship may disappear. In dynamic postural condition, lower-extremity muscle power could facilitate compensatory postural actions, limiting induced body imbalance likely to generate falls in older subjects. In young subjects, there could be a relationship between very early rapid torque of the leg extensor muscles and postural performance. In the case of postural reaction to (external) perturbations, a high percentage of type II muscle fibers could be associated with the ability to react quickly to postural perturbations in young subjects, while it may enable a reduction in the risk of falls in older subjects. In practice, in older subjects, muscle strength and/or power training contributes to reducing the risk of falls, as well as slowing down the involution of muscle typology regarding type II muscle fibers.